Zinc regulates microglial polarization and inflammation through IKBα after spinal cord injury and promotes neuronal repair and motor function recovery in mice - Li, Daoyong; Bai, Mingyu; Guo, Zhanpeng; Cui, Yang; Mei, Xifan; Tian, He; Shen, Zhaoliang (Frontiers in Pharmacology, 2025)
IntroductionSpinal cord injury (SCI) leads to severe inflammation and neuronal damage, resulting in permanent loss of motor and sensory functions. Zinc ions have shown potential in modulating inflammation and cellular survival, making them a promising therapeutic approach for SCI. This study investigates the mechanisms of zinc ion treatment in SCI, focusing on its effects on inflammation.MethodsWe used transcriptomic analysis to identify key pathways and genes involved in the inflammatory response in a mouse model of SCI. In vitro studies assessed the impact of zinc ions on inflammation, cell polarization, and apoptosis. IKBα expression was evaluated as a potential target of zinc ions, both in cultured cells and in vivo.ResultsTranscriptomic analysis revealed that zinc ions modulate inflammatory pathways through IKBα, which inhibits NF-κB activity. In vitro, zinc treatment upregulated IKBα expression, reducing inflammation, polarization, and apoptosis. These results were confirmed in the SCI mouse model, where zinc ions also reduced inflammation and cell death.DiscussionOur findings highlight a novel mechanism by which zinc ions regulate inflammation in SCI by upregulating IKBα and inhibiting NF-κB activation. This suggests potential therapeutic applications of zinc ions in SCI and other inflammatory conditions, warranting further investigation into their clinical benefits.